2020
DOI: 10.3390/cells9081805
|View full text |Cite
|
Sign up to set email alerts
|

PKHhigh/CD133+/CD24− Renal Stem-Like Cells Isolated from Human Nephrospheres Exhibit In Vitro Multipotency

Abstract: The mechanism upon which human kidneys undergo regeneration is debated, though different lineage-tracing mouse models have tried to explain the cellular types and the mechanisms involved. Different sources of human renal progenitors have been proposed, but it is difficult to argue whether these populations have the same capacities that have been described in mice. Using the nephrosphere (NS) model, we isolated the quiescent population of adult human renal stem-like PKHhigh/CD133+/CD24− cells (RSC). The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The first point of innovation of the present study lies in the use of a human NS model to investigate the role of the IL‐8‐CXCR1/2 axis. This model 15,35 represents in fact a unique tool and a human source of primary renal cells, with emphasis on podocytes, which are normally difficult to isolate and can be cultured only upon immortalisation 36 . In a previous study, Loretelli et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first point of innovation of the present study lies in the use of a human NS model to investigate the role of the IL‐8‐CXCR1/2 axis. This model 15,35 represents in fact a unique tool and a human source of primary renal cells, with emphasis on podocytes, which are normally difficult to isolate and can be cultured only upon immortalisation 36 . In a previous study, Loretelli et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a differential involvement of epithelial and podocyte cells in DN pathogenesis, which leads to a differential Ladarixin effect on epithelial cells, podocytes and leucocytes contribution to disease progression (Figure 5). This model 15,35 represents in fact a unique tool and a human source of primary renal cells, with emphasis on podocytes, which are normally difficult to isolate and can be cultured only upon immortalisation. 36 In a previous study, Loretelli et al showed that in vitro challenge of human immortalised podocytes with HG resulted in increased IL-8 secretion and DNA damage, and that this damage is prevented by CXCR1/2 blockade.…”
Section: Cd3+ T Lymphocytes Increase During the Progression Of Dnmentioning
confidence: 99%
“…These scaffolds allow for the investigation of cell-ECM interactions in specific organ or tissue microdomains. For example, the fate of pluripotent or progenitor cells in a recellularized scaffold can be followed to learn about specific cell differentiation determinants ( Du et al, 2016 ; Bombelli et al, 2018 ; Zhang et al, 2019 ; Bombelli et al, 2020 ; Ullah et al, 2020 ).…”
Section: New Strategies In In Vitro Modeling Of Ki...mentioning
confidence: 99%